CSF neurogranin as a neuronal damage marker in CJD: a comparative study with AD. Issue 8 (16th May 2019) - Blennow, Kaj; Diaz-Lucena, Daniela; Zetterberg, Henrik; Villar-Pique, Anna; Karch, Andre; Vidal, Enric; Hermann, Peter; Schmitz, Matthias; Ferrer Abizanda, Isidro; Zerr, Inga; Llorens, Franc
Abstract : Objective: To investigate whether cerebrospinal fluid (CSF) neurogranin concentrations are altered in sporadic Creutzfeldt-Jakob disease (CJD), comparatively with Alzheimer's disease (AD), and associated with neuronal degeneration in brain tissue. Methods: CSF neurogranin, total tau, neurofilament light (NFL) and 14-3-3 protein were measured in neurological controls (NCs, n=64), AD (n=46) and CJD (n=81). The accuracy of neurogranin discriminating the three diagnostic groups was evaluated. Correlations between neurogranin and neurodegeneration biomarkers, demographic, genetic and clinical data were assessed. Additionally, neurogranin expression in postmortem brain tissue was studied. Results: Compared with NC, CSF neurogranin concentrations were increased in CJD (4.75 times of NC; p<0.001, area under curve (AUC), 0.96 (95% CI 0.93 to 0.99) and AD (1.94 times of NC; p<0.01, AUC 0.73, 95% CI 0.62 to 0.82), and were able to differentiate CJD from AD (p<0.001, AUC 0.85, 95% CI 0.78 to 0.92). CSF tau was increased in CJD (41 times of NC) and in AD (3.1 times of NC), both at p<0.001. In CJD, neurogranin positively correlated with tau (r=0.55, p<0.001) and was higher in 14-3-3-positivity (p<0.05), but showed no association with NFL (r=0.08, p=0.46). CJD-MM1/MV1 cases displayed higher neurogranin levels than VV2 cases. Neurogranin was increased at early CJD disease stages and was a good prognostic marker of survival time in CJD. In brain tissue, neurogranin was detected in the cytoplasm, membrane and postsynaptic density fractions of neurons, with reduced levels in AD, and more significantly in CJD, where they correlated with synaptic and axonal markers. Conclusions: Neurogranin is a new biomarker of prion pathogenesis with diagnostic and prognostic abilities, which reflects the degree of neuronal damage in brain tissue in a CJD subtype manner.